Protein phosphatase PP1‐NIPP1 activates mesenchymal genes in HeLa cells. Issue 12 (20th April 2015) - Van Dessel, Nele; Boens, Shannah; Lesage, Bart; Winkler, Claudia; Görnemann, Janina; Van Eynde, Aleyde; Bollen, Mathieu
Abstract : The deletion of the protein phosphatase‐1 (PP1) regulator known as Nuclear Inhibitor of PP1 (NIPP1) is embryonic lethal during gastrulation, hinting at a key role of PP1‐NIPP1 in lineage specification. Consistent with this notion we show here that a mild, stable overexpression of NIPP1 in HeLa cells caused a massive induction of genes of the mesenchymal lineage, in particular smooth/cardiac‐muscle and matrix markers. This reprogramming was associated with the formation of actin‐based stress fibers and retracting filopodia, and a reduced proliferation potential. The NIPP1‐induced mesenchymal transition required functional substrate and PP1‐binding domains, suggesting that it involves the selective dephosphorylation of substrates of PP1‐NIPP1. Abstract : NIPP1 activates mesenchymal genes in HeLa cells. NIPP1 endows HeLa cells with contractile properties. The NIPP1‐induced transdifferentiation is mediated by protein phosphatase 1.